2016
DOI: 10.1177/0284185116641549
|View full text |Cite
|
Sign up to set email alerts
|

Visipaque – a Step Forward

Abstract: In a lecture in January 1896 WILHELM CONRAD ROENTGEN demonstrated a new kind of radiation (Xrays), which penetrated human tissue and blackened (or darkened) photographic films. In an early experiment, the X-rays had passed through the hand of his wife before impacting on a photographic film. On this film the shadow of the skeleton inside the fingers and the shadow of a metal ring around one of the fingers were whiter (brighter) and contrasted against the blacker (darker) shadows of the soft tissues of the fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Chemically, it is 5,5'-[(2-hydroxy-1,3-propanediyl) bis (acetylamino)]bis[N,N'-bis(2,3-dihydroxypropyl)-2,4,6-triiodo-1,3-benzenedicarboxamide] (Figure 1), with a molecular weight of 1550.20 and iodine content of 49.1%. It has six iodine atoms per molecule, no carboxyl groups and has nine hydroxyl groups evenly distributed around the molecule 8 . Iodixanol has a similar pharmacokinetic profile as other ICAs.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Chemically, it is 5,5'-[(2-hydroxy-1,3-propanediyl) bis (acetylamino)]bis[N,N'-bis(2,3-dihydroxypropyl)-2,4,6-triiodo-1,3-benzenedicarboxamide] (Figure 1), with a molecular weight of 1550.20 and iodine content of 49.1%. It has six iodine atoms per molecule, no carboxyl groups and has nine hydroxyl groups evenly distributed around the molecule 8 . Iodixanol has a similar pharmacokinetic profile as other ICAs.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…The toxicity of non‐ionic CM can primarily be attributed to direct chemotoxicity or to osmotic effects . Quintavalle et al .…”
Section: Introductionmentioning
confidence: 99%
“…recently suggested that CM induces apoptosis via three pathways, initially by triggering increased production of ROS, followed by activation of stress kinases and eventually by the intrinsic apoptosis pathway. It is generally recognized that CM have direct cytotoxic effects in vitro on renal tubular cells and vascular endothelial cells . It has further been demonstrated in vitro that direct CM‐induced cell damage can lead to oxidative stress and production of free radicals that can stimulate the tubuloglomerular reflex with possible negative consequences for in vivo renal perfusion.…”
Section: Introductionmentioning
confidence: 99%